3D hierarchical Co3O4@Co3S4 nanoarrays as cathode materials for asymmetric pseudocapacitors. Issue 9 (3rd February 2016) - Liu, Bo; Kong, Dezhi; Zhang, Jun; Wang, Ye; Chen, Tupei; Cheng, Chuanwei; Yang, Hui Ying
Abstract : A Co3 O4 @Co3 S4 nanoarray electrode is designed by a facile solution synthesis approach and investigated as a cathode material for an ASC. Abstract : Three-dimensional (3D) hierarchical Co3 O4 @Co3 S4 nanoarrays (NAs) were synthesized via a stepwise hydrothermal method involving precipitation and in situ sulfurization of Co3 O4 nanoneedle arrays (NNAs). By controlling both anion exchange and Ostwald ripening reactions during the sulfurization process, 3D hierarchical Co3 O4 @Co3 S4 NAs with tailored Co3 S4 nanostructures have been fabricated as electrode materials for electrochemical capacitor applications. Owing to an interconnected matrix within the 3D architecture, the as-prepared Co3 O4 @Co3 S4 NAs exhibit excellent electrical conductivity, high specific capacity and high cycling stability. It can deliver a high capacitance of 1284.3 F g −1 at 2 mV s −1 and maintain a capacitance retention of 93.1% after 5000 cycles. Moreover, a flexible solid-state asymmetric supercapacitor (ASC) composed of Co3 O4 @Co3 S4 NAs as the positive electrode and activated carbon (AC) as the negative electrode exhibited an energy density of 1.5 mW h cm −3 and a power density of 6.1 W cm −3 at a high operating voltage of 1.6 V. Our results not only present the 3D hierarchical nanostructure of Co3 O4 @Co3 S4 NAs, but they also demonstrate the potential of electrodes for future generation supercapacitors.